Cholesterol and sterols in molluscan endocrinology: past, present, future - Fodor, István; Markov, Gabriel V.; Yañez-Guerra, Luis Alfonso; Elekes, Károly; Pollák, Edit; Molnár, László; Pirger, Zsolt (Frontiers in Endocrinology, 2025)
Recently, critical evaluations have challenged the presence of vertebrate-type sex steroid signaling in mollusks, underlying the need of new research lines to shed light on molluscan endocrinology. The investigation of cholesterol metabolism and the potential biological role of sterols in mollusks has emerged as a growing research field in recent years. However, there is no clear consensus on several aspects of this topic and there is a great lack of relevant molecular data. In this perspective paper, we present an overview of our current knowledge on the role of cholesterol and sterols in mollusks and try to outline possible future research directions in molluscan endocrinology. Our study also provides a framework for studying cholesterol synthesis, uptake, transport, and metabolism in mollusks.